The construction and assumptions made about Egyptian women by development organizations - Gagnier, Christina (AUC Knowledge Fountain, 2013)
Since the inception of international human rights, some activists have argued for a universal framework and this framework has encountered resistance. International feminism is a space where the concept of universal truth begins to unravel. Feminists from the First World, purporting to speak on behalf of all women, essentialized the international woman’s experience and set an agenda based on their First World experience. Third World women critiqued the systematic exclusion of their voices from the dominant feminist discourse. The international human rights agenda shares many goals with economic development. Economic development can be a vehicle through which universal human rights are created in the Third World. More importantly, economic development shapes and describes an economy. Women, viewed by economic development, are consumers and producers of future consumers and future economic sectors. They are both shaped by and define the economy. In order to properly understand the intersection of the Third and First World, it is helpful to look at how the powerful actors, such as economic development agencies, construct women. In order to explore the relationship between economic development and Third World women, this paper will analyze World Bank development reports from Egypt. The reports date from the moment Egypt became an object of development in the 1950s to the present. The analysis will demonstrate the World Bank’s construction of Egyptian women. While throughout history, the locus of women’s oppression has been complex and changing, the World Bank has failed to understand Egyptian women as having agency over their own lives. Egyptian women are seen as being helpless victims, needing international intervention to act on their behalf.